PHP PROGRAMMING USING WEB SITES IN BEM STMIK JAKARTA STI & K - Arie Prihandika; Linda Wahyu Widianti, Skom, MMsi (Jurnal Sistem Informasi, 2007)
Student Execut ive Board is a student organization that requires a two-way communication with the students effectively, it is very beneficial to the organization and the students themselves. By using the conventional information media, making the data access time and place Seta inflexible in the maintenance of older information. The constraint that becomes the main problem as well as student organizations on campus STMIK  Jakarta STI & K. submission of information through the web is one solution that can solve these problems.  Delivery and storage of information is easy, flexible, and dynamic through the CMS (Content Management Services), established by utilizing web programming PHP (Personal Home Page) that supports MySQL crate database system. With the facility is a forum that is more value added features that make the web become interactive.